2019
DOI: 10.1016/j.erap.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural validation of a French version of the Emotional Processing Scale (EPS-25)

Abstract: Validation française de l'Echelle des Processus Emotionnels (EPS-25) Résumé Objectif: l'Echelle des Processus Emotionnels (Emotional Processing Scale-EPS) est un autoquestionnaire de 25 items utilisé pour évaluer les styles de traitement émotionnels et leurs dysfonctionnements. Notre objectif était de traduire et de valider cette échelle en français auprès d'une population tout venant et clinique. Méthode: après une traduction et une rétrotraduction, l'étude de validation a été menée auprès de 1176 adultes (21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 70 publications
2
24
3
Order By: Relevance
“…Regarding emotional processing (see Table 2), the EPS-25 total score indicated dysfunctional processing (M = 3.65, SD = 1.88) compared to the general population (M = 2.51, SD = 1.04), with the mean of the clinical sample nearing two standard deviations below the mean of healthy controls. All subscale scores were significantly different from those obtained by healthy controls (Gay et al, 2019) . The average scores obtained on the unprocessed emotions dimension were particularly high, indicating intrusive and persistent emotional experiences, which may be an indicator of a traumatic experience.…”
Section: Patientscontrasting
confidence: 81%
See 2 more Smart Citations
“…Regarding emotional processing (see Table 2), the EPS-25 total score indicated dysfunctional processing (M = 3.65, SD = 1.88) compared to the general population (M = 2.51, SD = 1.04), with the mean of the clinical sample nearing two standard deviations below the mean of healthy controls. All subscale scores were significantly different from those obtained by healthy controls (Gay et al, 2019) . The average scores obtained on the unprocessed emotions dimension were particularly high, indicating intrusive and persistent emotional experiences, which may be an indicator of a traumatic experience.…”
Section: Patientscontrasting
confidence: 81%
“…In the original English version of the EPS developed in the United Kingdom, these five factors explained 59.4% of the total variance, and overall internal reliability was high (α = 0.92), ranging from 0.70 to 0.80 for the five factors. A French version has been developed (Gay et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Emotional Processing Scale (EPS-25) Baker et al (2010) and Gay et al (2019) measures five facets of emotional processing (Impoverished Emotional Experience, Signs of Unprocessed Emotion, Avoidance, Suppression, and Unregulated Emotion). Items are rated from 0 (completely disagree) to 9 (completely agree) and averaged for each subscale.…”
Section: Methodsmentioning
confidence: 99%
“…Despite EAET's effectiveness, little is known about the mechanisms by which EAET achieve its effects. In theory, emotional processing is a key mechanism (Lumley and Schubiner, 2019), as deficits in emotional processing have been identified in patients with chronic pain and IBS (Baker et al, 2010;Esteves et al, 2013;Phillips et al, 2013;Gay et al, 2019), and problems in emotional processing have been found to mediate the association between childhood adversity and the development of psychiatric (Chung and Chen, 2017) and somatic symptoms (Mozhgan et al, 2020). Facets of emotional processing, such as emotional differentiation, naming, experiencing, tolerating, and expression, are believed to be a core mechanism in psychodynamic treatments of certain conditions (Messer, 2013;Høglend and Hagtvet, 2019).…”
Section: Introductionmentioning
confidence: 99%